FEATURES OF MANAGEMENT OF THE PERSON, TEAM AND GROUP IN THE SPHERE OF HOUSING AND COMMUNAL SERVICES - U. Slinyakow (Вестник университета)
The article describes the main approaches to control a person, team and group in the sphere of housing and communal services, the analysis of current practice development of internal regulations, of the proposal to develop a "code of business ethics for employees, filing requirements for employee accounting services.